Correlation Between Pranayam and Occurrence of Covid-19: An Observational Study: Life Sciences -Ayurveda - Deulkar, Nikita; Misar Wajpeyi, Dr.Sadhana (International Journal of Life Science and Pharma Research, 2023)
Due to the widespread COVID-19 outbreak, people are consistently exposed to difficult circumstances and are morelikely to become infected. Yoga includes the practice of Pranayama, which is a method of controlled breathing. It is well known toboost immunity and lessen illness. However, there has yet to be a scientific investigation on the effectiveness of Pranayama inavoiding COVID-19. This research aimed to study the association between Pranayam and the occurrence of COVID-19. Thestudy's objectives are to increase awareness amongst the population regarding the importance of practicing Pranayam forstrengthening respiratory system functions and immunity. A cross-sectional study was conducted among 100 Subjects betweenthe age groups 18 to 60. Group A comprises subjects practicing daily Pranayama, and Group B is not practicing Pranayama. Thenincidence of COVID in both groups was assessed based on diagnostic criteria by filling out pre-designed proforma, and acomparison was made by statistical analysis. Subjects in Group A practicing daily Pranayama showed less percentage of COVID-19 infection. Also, the positive subjects had no symptoms, or the severity of symptoms was less than Group B subjects notpracticing Pranayama. The comparison of the groups was statistically significant. It may be due to increased strength and immunityin subjects practicing Pranayama. This study concluded that Pranayama proved beneficial in the prevention and fought againstCOVID infection.Keywords: , , , , Pranayama, Yoga.